What can COVID‐19 teach us about patient satisfaction in the emergency department? A mixed‐methods approach - Maureen O. Grissom; Morgan Farra; Eric S. Cruzen; Erin Barlow; Sanjey Gupta (Journal of the American College of Emergency Physicians Open)
Abstract Objective The current study explored improved patient satisfaction scores at a single emergency department (ED) during the early phase of the COVID‐19 pandemic (March to May 2020). Methods A mixed‐methods design, integrating qualitative and quantitative data analyses, was employed to explore a total of 289 patient satisfaction survey ratings and 421 comments based on care that took place in the ED during the initial phase of the COVID‐19 epidemic. This allowed for comparisons to a more typical time period in the ED along with the emergence of novel categories of influence. Results The ED census was 31% lower during 2020 (COVID‐19) than the previous year, and a significantly greater percentage of patients in 2020 indicated that they would “definitely recommend” the ED compared with 2019. Wait time was mentioned in >40% of dissatisfied patient comments in 2019 but <20% of dissatisfied patient comments in 2020. General negative comments were proportionately greater than general positive comments in 2019, whereas in 2020 the reverse pattern held. Other categories did not differ significantly across 2019 and 2020. Conclusions The general circumstances surrounding the early stages of the COVID‐19 pandemic included a lower census in the ED and higher reported satisfaction among patients. A comparison of the content of patient comments revealed less concern about wait times and a more positive overall view toward receiving care during the first 3 months of the pandemic.